Menimbang Masa Depan Hukum Islam Dalam Pembentukan Hukum Internasional Via Mahkamah Internasional - Eka An Aqimuddin (Fakultas Hukum Universitas Islam Indonesia, 2024)
Apart from the state, the International Court of Justice (ICJ) also plays a significant role in shaping international law through its rulings and legal advisors. Article 38 of the ICJ Statute states that the ICJ is nevertheless only permitted to use traditional legal sources to perform its duties. In order to achieve the universalism of international law, the Court, as an organization that represents legal systems around the world, ought to be permitted to rely on Islamic law as one of its legal sources when performing its duties. Consequently, Islamic law can be represented in developing international law. This article proposes the potential influence of Islamic law on the development of international law in the future through the ICJ. Through an inter-civilizational perspective, international law can be understood as a discourse among different civilizations worldwide. In this context, Islamic law must actively participate in this debate as a representative of a legal system and identity.